Countertransference, alliance, and outcome in the treatment of patients with personality disorder: a longitudinal naturalistic study - Breivik Øvstebø, Randi; Pedersen, Geir; Wilberg, Theresa; Røssberg, Jan Ivar; Johnsen Dahl, Hanne-Sofie; Kvarstein, Elfrida Hartveit (Frontiers in Psychiatry, 2024)
ObjectiveRelational dynamics, including countertransference responses and the therapeutic alliance, are crucial in the treatment of patients with personality disorders (PD). However, few studies on PD treatment focus on the dyadic process of therapy. The present study aims to investigate associations between therapist emotional response/countertransference (CT) and patients’ experience of treatment alliance, and CT developments in therapies with treatment completion as outcome.MethodA longitudinal, observational study of patients (N = 365) treated at PD treatment units within specialist mental health services. CT was assessed repeatedly during therapy by the Feeling Word Checklist – Brief Version with three subscales—Inadequate, Confident, and Idealized. Early alliance was assessed after 6 months of treatment (Working Alliance Inventory, WAI). Treatment completion was defined as completing treatment according to schedule versus not completing treatment. Statistical analyses included Linear Mixed Models.ResultsIn the early phase of therapy, lower WAI predicted lower levels of Confident, Idealized, and higher Inadequate CT. The relation between early WAI and CT levels during treatment remained stable. The development of CT during treatment differed according to treatment completion with significant trends of increasing Inadequate CT and decreasing Idealized CT in not completed treatments. WAI and treatment completion had strong and independent effects. Further moderator analysis did not yield additional information.ConclusionThe study demonstrates significant associations between negative CTs and lower patient-rated WAI in the early phase of therapy, and a development of increasingly more negative CTs during therapy in treatments which were not completed according to schedule. The results indicate high clinical relevance of monitoring therapeutic relationships in PD treatments. Further research on the emotional and relational quality of psychotherapeutic relationships in PD treatments is needed.